Collaborative public procurement: Institutional explanations of legitimised resistance. Issue 3 (September 2016) - Meehan, Joanne; Ludbrook, Michael N.; Mason, Christopher J.
Abstract: This paper reports on the barriers to regional collaborative procurement developed from an action research study of five UK public authorities in the emergency services sector. Despite political pressure to procure collaboratively, strategic avoidance responses of institutional logics and symbolic tick boxing legitimise stakeholder resistance to isomorphic forces and entrench operational barriers. The prevailing institutional logics are that regional collaborative procurement is unsuitable and risky, derived from procurement's lack of status and the emotive nature of the emergency services. Symbolic tick boxing is seen through collaboration that is limited to high profile spend categories, enabling organisations to demonstrate compliance while simultaneously retaining local decision-making for less visible, but larger areas of spend. The findings expose choice mechanisms in public procurement by exploring tensions arising from collaborative procurement strategies within, and between, organisations. Multiple stakeholders' perspectives add to current thinking on how organisations create institutional logics to avoid institutional pressure to procure collaboratively and how stakeholders legitimise their actions. Highlights: Multidimensional operational barriers exist to collaborative public procurement. Collaborative public procurement creates conflicts of legitimacy. Tensions arise from collaborative procurement within, and between, organisations.